Activity design for improving mathematical understanding - Çelik Görgüt, Rahime (Mehmet Akif Ersoy Universitesi Egitim Fakultesi Dergisi, 2025)
This study aims to present a conceptual framework on the design of activities to improve comprehension and evaluate the impact of activities developed on students' mathematical understanding. Conducted as a case study in the theoretical dimension, the activities developed within the scope of the study were applied to 21 8th grade students determined by convenience sampling method. The data obtained were analysed according to whether the students used algorithms correctly, came up with multiple solutions, made logical inferences and discoveries, made connections with daily life, made use of multiple representations, established relationships between concepts, and were able to recognize the need for a concept in history and produce solutions for it. The results of the study showed that the designed activities were effective in improving students' mathematical understanding.